Efektivitas Komunikasi Penyuluhan terhadap Tingkat Kepuasan Petani di Desa Watludan Kabupaten Maluku Tengah - Salestina Wewra; Risyad Albert Far-Far; Paulus M Puttilehalat (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Watludan Village is located in Teon Nila Serua District, Central Maluku Regency, Maluku Province. Extension communication activities and agricultural programs provided by the government have also been carried out by extension workers, but the availability of extension workers is still lacking in the area, so it becomes one of the influencing factors. Extension communication can increase farmers' knowledge and renewable skills in managing crop yields, ultimately increasing farmer satisfaction. This research evaluates the effectiveness of communication extension service farmers' satisfaction in Watludan Village. Quantitative research method with Spearman rank correlation analysis and research period 16 November - 11 December 2023, sample determination was conducted through purposive sampling of farmers engaged in agricultural activities, with a sample size that includes 14 farmers present in the area. The results of the study indicate that overall, the effectiveness of extension is not optimal because many respondents are still in the "Less Good" and "Enough" categories in terms of acceptance, understanding of messages, changes in attitudes, changes in behavior, and feedback. The satisfaction level among farmers regarding the effectiveness of extension workers remains low, with the majority of farmers feeling less satisfied with the three aspects. There is a significant and positive influence between the effectiveness of extension communication and the level of farmer satisfaction. This research assesses how extension communication impacts farmer satisfaction in Watludan Village, central Maluku Regency.